Раскопки „казармы” в портовом районе Херсонеса в 1993 г. - Дьячков, С.В.; Золотарев, М.И. (My University, 1994)
Dyachkov S. V., Zolotaryov M. I. Excavations of the "Barrack" at the Port-Side of Chersonessus in 1993